(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Activimeters (or dose calibrators) are essential instruments to verify activity of radiopharmaceutical after production and also before the dose administration in humans or animals for molecular imaging. The efficiency and safety measurements depend on, beside other factors, constancy tests and quality assurance. Thereby, the aim of this work was to perform constancy tests and quality assurance in the activimeters of the UPPR/CDTN, based on the CNEN-NN 3.05 Brazilian standard and the manufacturer’s manual. Physical inspection, auto zero, background check, camera voltage, data check and constancy test were done. In addition, accuracy and precision tests were performed using a set of standard certified radioactive sources (57Co, 133Ba and 137Cs), according to the CNEN NN 3.05 Brazilian standard. Linearity test was also performed to evaluate the response of the equipment in over the entire range of activities used in routine. The equipments are periodically submitted to the quality control tests and the results were compared. After performing the proposed tests it is possible to conclude that activimeters are in accordance with the requirements of the CNEN standard and manufacturer´s manual. A quality control checklist was prepared to guide users and to record the results of quality assurance testing to monitor the equipment performance. This initiative is part of the quality assurance program implemented at UPPR.